1988
DOI: 10.1104/pp.86.2.332
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Changes in Protein Phosphorylation Associated with Light-Induced Gravity Perception In Corn Roots

Abstract: The effect of light and calcium depletion on in vivo protein phosphorylation was tested using dark-grown roots of Merit corn. Light caused rapid and specific promotion of phosphorylation of three polypeptides. Pretreatment of roots with ethylene glycol bis N,NN',N' tetrmacetic acid and A23187 prevented light-induced changes in protein phosphorylation.We postulate that these changes in protein phosphorylation are involved in the light-induced gravity response.Significant advances have been made in our understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1989
1989
1992
1992

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…In roots, light-, calcium-, and calmodulin-dependent phosphorylation of specific peptides have been reported, supporting the view that in plants, as in other eukaryotes, protein kinases transduce environmental stimuli (10,13). Because these data suggest a role for calcium as a second messenger in plants (13) it is probable that specific calcium-dependent protein kinases ubiquitous in other eukaryotes (e.g.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…In roots, light-, calcium-, and calmodulin-dependent phosphorylation of specific peptides have been reported, supporting the view that in plants, as in other eukaryotes, protein kinases transduce environmental stimuli (10,13). Because these data suggest a role for calcium as a second messenger in plants (13) it is probable that specific calcium-dependent protein kinases ubiquitous in other eukaryotes (e.g.…”
supporting
confidence: 53%
“…For both of these stimuli the root cap is believed to be the site ofperception, and also is hypothesized involved with the transduction of the stimulus leading to a particular developmental response. Recent studies have revealed that a few specific proteins are rapidly phosphorylated in response to light and calcium application, and that calmodulin is probably involved in this response (10,14). Here we present further evidence for the existence of a second messenger-dependent protein kinase in maize roots, and also describe the primary structure and the spatial distribution of gene expression within a tissue known to transduce a variety of environmental stimuli.…”
Section: Discussionmentioning
confidence: 71%